Study of histopathological features and proliferation markers in cases of Wilms′ tumor - Das, Ram Narayan; Chatterjee, Uttara; Sinha, Swapan K; Ray, Ashoke K; Saha, Koushik; Banerjee, Sugato (Indian Journal of Medical and Paediatric Oncology, 2012)
Context: The spectrum of pediatric renal tumors is different from adult renal tumors, and Wilms′ tumor (WT) forms the majority. The histological type and clinicopathological staging are the two important prognostic parameters. The role of newer prognostic factors is not clear. Aims: This study was performed to analyze the histopathological spectrum of pediatric renal tumors and to study the expression of proliferation markers (Ki-67 and p53) in WT and correlate its expression in epithelial and blastema components in different stages. Materials and Methods: Twenty-seven cases of pediatric renal tumors were collected over 2 years. Hematoxylin-eosin staining was used for diagnosis. Immunostaining was performed for Ki-67 and p53. Ki-67 proliferation index (PI) and p53 expression were determined in each case and for the epithelial and blastema components separately. Statistical Analysis and Results: We had 20 cases of WT (74.1%), three cases of mesoblastic nephroma (11.1%), three cases of clear cell sarcoma (11.1%) and one case of rhabdoid tumor (3.7%). It was observed that the PI of the epithelial component (57.2%) was significantly higher than that of blastema (39.53%) in all stages. The PI in Stage II is significantly higher than that in Stage I. Statistical analysis could not be performed in Stages III and IV due to the small number of cases. p53 expression did not show any significant difference in the epithelial and blastema components. There was also no significant difference between the stages. Conclusion: In this study, we found the differences between PI of different tissue components of WT, with the epithelial component having a higher PI, which correlated with the stage of advancement of the disease.
Keywords: Ki-67; prognosis; p53; Wilms′ tumor